Genetic Loci Conferring Reducing Sugar Accumulation and Conversion of Cold-Stored Potato Tubers Revealed by QTL Analysis in a Diploid Population - Xiao, Guilin; Huang, Wei; Cao, Hongju; Tu, Wei; Wang, Haibo; Zheng, Xueao; Liu, Jun; Song, Botao; Xie, Conghua (Frontiers in Plant Science, 2018)
Cold-induced sweetening (CIS) caused by reducing sugar (RS) accumulation during storage in low temperature in potato tubers is a critical factor influencing the quality of fried potato products. The reconditioning (REC) by arising storage temperature is a common measure to lower down RS. However, both CIS and REC are genotype-dependent and the genetic basis remains uncertain. In the present study, with a diploid potato population with broad genetic background, four reproducible QTL of CIS and two of REC were resolved on chromosomes 5, 6 and 7 of the CIS-sensitive parent and chromosomes 5 and 11 of the CIS-resistant parent, respectively, implying that these two traits may be genetically independent. This hypothesis was also supported by the colocalization of two functional genes, a starch synthesis gene AGPS2 mapped in QTL CIS_E_07-1 and a starch hydrolysis gene GWD colocated with QTL REC_B_05-1. The cumulative effects of identified QTL were proved to contribute largely and stably to CIS and REC and confirmed with a natural population composed of a range of cultivars and breeding lines. The present research identified reproducible QTL for CIS and REC of potato in diverse conditions and elucidated for the first time their cumulative genetic effects, which provides theoretical bases and applicable means for tuber quality improvement.